Avaliação da produtividade de uma linha de pintura de veículos por meio de simulação e análise financeira - Drevek, Paulo Roberto (2016)
This study evaluates the possibility of increasing the productivity of a vehicle painting line located in the region of Curitiba, PR, Brazil. The studied painting line has a total of 117 stations, where 30 of them are buffer stations. The line is powered by two types of vehicles, which can be painted in several solid or metallic colors, according to demand. A significant difference occurs, however, between the treatments of paintings. A production mix (quantity and sequencing) involving solid colors and metallic colors share the same line. Moreover, metallic colors require additional steps due to the application of varnish after painting. In this case, the same robots perform both: painting and application of varnish coating. Differences in cabins’ processing times at stations may cause idle times along the painting line, a fact evaluated in the presented study. There are also other reasons for idleness as rework fixes, startup conditions (warm-up), and uncertainties in the supply line. The mentioned uncertainty can cause impact on income and, consequently, losses in production capacity. By means of the simulation model, the viability of alternative solutions for the problem is evaluated. The approach used is twofold: i) a discrete event simulation is performed using SIMIO® software, which identifies the formation of production bottlenecks and it suggests conditions for increasing productivity; and, ii) a financial analysis is performed in order to scale the maximum investment, according to the company’s criteria, to enable productivity increase indicated by the discrete event simulation. So, while the simulation model aims to determine how the process is affected by variations in processing times at stations, supply conditions of the line, sequencing, rework and the output of painted vehicles, financial analysis indicates whether the suggested increase in productivity is feasible to be implemented from the point of view of required investment and return to the company. For the case study, the company has provided data from six months of painting line operations. The results obtained by simulation suggest the possibility of productivity increase of 10% acting on specific points of the line (e.g., detected bottleneck position). The financial analysis indicates the necessary investments for such optimized production condition. The obtained results in this study suggest a systematic assessment of the feasibility of projects in the context of the automotive industry.